2016
DOI: 10.1002/jcla.21922
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hemogram of Radiation Workers in Tangshan, China

Abstract: Long-term IR has some effects on the health of radiation workers, thus protective measures should be further strengthened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
5
1
1
Order By: Relevance
“…36 Another report revealed that the level of RBCs and hemoglobin markedly decreased with longer duration of employment of radiation workers in Tangshan, China. 37 However, in the present study, the males' RBCs and hemoglobin in both sexes did not change with longer length of service. This finding may be due to the different kinds of radiation workers, which included medical staffs and industrial workers in the Tangshan study, whereas the radiation workers in the present study only came from hospital.…”
Section: Discussioncontrasting
confidence: 67%
“…36 Another report revealed that the level of RBCs and hemoglobin markedly decreased with longer duration of employment of radiation workers in Tangshan, China. 37 However, in the present study, the males' RBCs and hemoglobin in both sexes did not change with longer length of service. This finding may be due to the different kinds of radiation workers, which included medical staffs and industrial workers in the Tangshan study, whereas the radiation workers in the present study only came from hospital.…”
Section: Discussioncontrasting
confidence: 67%
“…46 However, with the increase of the cumulative dose, the counts of radiologists such as RBC, WBC, PLT, and HB were significantly decreased, which was partially different from our study. 41 Overall, changes in RBC counts occurred earliest, with a typical turning point at a radiation dose of 2.000 mSv, which was well below the ICRP limit. 12 This result prompted us to focus on how the lowest range of radiation doses affects blood profiles.…”
Section: Discussionmentioning
confidence: 89%
“…It is also worth mentioning that the results of the Tangshan study showed that the type and dose of radiation the radiation workers were exposed to differed among different job types, as did the blood profiles. 41 This suggests that we can explore the correlation between the type of work and the health of radiation workers in the future. Thus, the peripheral blood profiles of workers exposed to long-term low-dose ionizing radiation may be affected by a variety of factors, consistent with the human epidemiological and clinical findings that low-dose ionizing radiation and individual health effects are influenced by demographics, genetics, radiation components, sources, lifestyle, and other environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the peripheral hemogram might also indicate radiation-induced tissue damage 16,17 ; however, most peripheral blood cells including WBCs and LYMs were not found to significantly differ between the mortality and survival groups. This suggests that the general loss of peripheral blood or immune cells might not be the major reason for lethality.…”
Section: Discussionmentioning
confidence: 98%